Okulare Demokratie: Der Bürger als Zuschauer - Kajewski, Marie-Christine; Hammer, Dominik (transcript, 2017)
In The Eyes of the People the political scientist Jeffrey Edward Green develops a fundamentally new theory of democratic participation termed "ocular democracy«, emphasizing the citizens' view as an instrument of democratic control that does not focus on contents but rather on the public performance of leading politicians. Presenting that theory about democracy, this volume makes its approach as well as the debate about it accessible to the German context of discourse for the first time. The contributors take up the debate about the crisis of representative democracy and examine the potential a plebiscitary democracy of viewers may have.